Simulation-Based Tracking Test and Optimization of Large-Tonnage Box Girder Transport with Trolley on an Erected Bridge - Lei Wang; Zhong-da Lv; Ai-min Xu; Fei Wang; Xin-long Dong (Advances in Civil Engineering)
In the construction of large-tonnage box girder, the construction load of box girder transport is generally greater than the operating load in highway industry; therefore, it is a crucial task to carry out accurate simulation and optimization on bearing box girder. For this purpose, the refined modeling method of 40 m/1270t box girder is studied first in this paper, followed by detailed stress analysis by considering the impact coefficient of vehicles and the most unfavorable conditions. Tracking tests on dead load, prestressed load, and the transport load have shown that the calculated stress values obtained by the refined models are very close to the measured stress values. Based on dynamic strain test of the vehicles at the speed of 4 km/h, the impact coefficient of four vehicles is estimated to be 1.08 and its value meets the requirements of no more than 1.1 provided by the vehicle manufacturer. Aimed at no tensile stress in the midspan section, the optimized geometry of 40 m box girder is obtained with less concrete and longitudinal prestressed tendons. These results demonstrate the plausibility and validity of the proposed research methods and optimization schemes for large-tonnage box girder transport.